2021
DOI: 10.3389/fnut.2021.634410
|View full text |Cite
|
Sign up to set email alerts
|

Food Oral Processing—An Industry Perspective

Abstract: We illustrate how scientific understanding of Food Oral Processing enables food product development with specific benefits for several target populations. in vivo, in vitro, and in silico approaches are discussed in the context of their ability to quantify oral processing from the molecular to the macroscopic scale. Based on this understanding, food structures with enhanced performance in terms of hedonic and nutritional properties as well as appropriateness for age and certain medical conditions can be develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…As 3-D food printers utilize computer-aided design (CAD) to digitally create 3-D models of food to be printed, it should be possible to integrate CAFE models into the system. Personalized nutrition is likely the next frontier and could benefit from CAFE approaches 94 , including the framework elaborated here.…”
Section: -D Food Printing and Personalizationmentioning
confidence: 99%
“…As 3-D food printers utilize computer-aided design (CAD) to digitally create 3-D models of food to be printed, it should be possible to integrate CAFE models into the system. Personalized nutrition is likely the next frontier and could benefit from CAFE approaches 94 , including the framework elaborated here.…”
Section: -D Food Printing and Personalizationmentioning
confidence: 99%
“…Food texture has been defined by International Organization for Standardization (ISO) in its standard vocabulary for sensory analysis as all rheological and structural (geometric and surface) attributes of a food product perceptible through mechanical, tactile, visual, and auditory receptors (ISO, 2008). The texture is also related to the sensations experienced as food is transformed in the oral cavity (Devezeaux De Lavergne et al, 2021;Liu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The perception of food is reflected in the way it is chewed. Researchers addressed the issue of oral processing, which involves determining mouth movements, required muscle work, or food properties after chewing (Devezeaux De Lavergne et al, 2021; Funami et al, 2014; Guo, 2021; He et al, 2022; Lillford, 2018). Scientists have studied various mechanical properties in isotropic/unstructured samples: Koç et al (2019) tested the rheology of hydrocolloid gels, Aguayo‐Mendoza et al (2021) examined cheese with filler particles, Le Révérend et al (2016) found links between hardness differences and oral processing of bread and biscuits, and Kohyama et al (2007) could show the influence of the particle size of vegetables on mastication physics.…”
Section: Introductionmentioning
confidence: 99%